Sistem Informasi Pemesanan dan Pemasangan Aluminium dan Kaca Berbasis Web pada Ical Karya Kaca Aluminium - Ulum, Khoirul; Hati, Kusuma; Aristejo (Jurnal Sistem Informasi, 2025)
This study establishes a web-based information system for ordering aluminum and glass for Ical Karya Kaca Alumunium. The objective is to enhance operational efficiency and customer satisfaction during the ordering process. The methodology encompasses requirements analysis, system design, and validation. The system enables customers to conveniently place orders online, select products, and arrange installations. Evaluation results indicate that the system enhances order processing speed and accuracy, facilitating improved communication between customers and the company. Additionally, the user-friendly interface elevates user satisfaction levels. The system's implementation enhances internal efficiency and offers a competitive market advantage. Consequently, this information system serves as an innovative solution to fulfill customer demands and bolster the growth of Ical Karya Kaca Alumunium amidst a competitive landscape.